Extremophiles as a Model of a Natural Ecosystem: Transcriptional Coordination of Genes Reveals Distinct Selective Responses of Plants Under Climate Change Scenarios - Bajay, Stephanie K.; Cruz, Mariana V.; da Silva, Carla C.; Murad, Natália F.; Brandão, Marcelo M.; de Souza, Anete P. (Frontiers in Plant Science, 2018)
The goal of this research was to generate networks of genes co-expressed to explore the genomic responses of in Rhizophora mangle L. populations to their contrasting environments and to understand the capacity of adaptation of this true mangrove species in the face of historical and future perturbations and climatic changes. RNA sequencing data were generated for R. mangle samples from the extremes of the climate in Brazil: equatorial and subtropical regions. A gene co-expression network was constructed using Pearson's correlation coefficient, showing correlations among 78,364 transcriptionally coordinated genes. Each region exhibited two distinct network profiles: genes correlated with "oxidative stress response" were positively expressed in subtropical samples, whereas genes correlated with "hyperosmotic salinity response", "heat response" and "UV response" were positively expressed in equatorial samples. A total of 992 clusters were enriched for ontology terms indicating that R. mangle is under higher stress in the equatorial region. Increased heat may thus pose a great risk to species diversity at its distribution centre in the Americas. This study under natural field conditions allowed us to associate specific responses of genes previously described in controlled environments with their responses to the local habitat in which the species survives. This work highlights that mangroves are good models for understanding the interactions between the threats of climate change and the genomic responses at different scales for natural plant ecosystems. The different impacts presented in the extremes of regional variation show how climate change factors impact the structure, biodiversity and gene regulatory responses of plants.